2021
DOI: 10.1080/09687599.2021.1994373
|View full text |Cite
|
Sign up to set email alerts
|

Leadership for change: pathways to activism for African women with disability

Abstract: In African countries, women with disability encounter severe discrimination as their devalued status as women intersects with negative and hostile community attitudes toward disability. Women with disability who are engaged as leaders in the disability movement play a vital role in addressing this discrimination. Through in-depth interviews, this study examined barriers and pathways to leadership encountered by women with disability from Tanzania, Ghana, and Kenya who were active within the disability movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Accordingly, disabled women are often encouraged to be 'childlike' and 'passive' (Ghai, 2003: 19), often presented as recipients of paternalistic policies, rather than as architects of state governance. Research from Africa and Europe has found that disabled women have to work hard to overcome negative stereotypes in order to 'convince' others that they are capable of leadership (González, 2009;King et al, 2021). These stereotypes -as well as the marginalisation of disabled women in both the women's movement and the disability rights movement -are experienced globally, as Anita Ghai (2003: 18) observes in her study of gender and disability in India, though, of course, these stereotypes also sit alongside local iterations.…”
Section: Gender Disability and Intersectional Approaches To Political...mentioning
confidence: 99%
“…Accordingly, disabled women are often encouraged to be 'childlike' and 'passive' (Ghai, 2003: 19), often presented as recipients of paternalistic policies, rather than as architects of state governance. Research from Africa and Europe has found that disabled women have to work hard to overcome negative stereotypes in order to 'convince' others that they are capable of leadership (González, 2009;King et al, 2021). These stereotypes -as well as the marginalisation of disabled women in both the women's movement and the disability rights movement -are experienced globally, as Anita Ghai (2003: 18) observes in her study of gender and disability in India, though, of course, these stereotypes also sit alongside local iterations.…”
Section: Gender Disability and Intersectional Approaches To Political...mentioning
confidence: 99%
“…Work placement programmes, which should help them make a smooth transition from school to employment, must be designed especially for students with disabilities. Many women with disabilities struggle with workplace expectations that often affect their overall wellbeing (King et al, 2021; Lindsay et al, 2021b). There may also be high expectations on the part of businesses, especially regarding social competence and comprehension of business operations (Edmonds et al, 2021).…”
Section: The Stakeholdersmentioning
confidence: 99%